The Reality of The Modern Information Systems of the Participating Sports Clubs in The Iraqi Football Premier League (2020-2021) - Mohammed, Raad; Ali , Mohsin (Journal of Physical Education, 2022)
The research aimed to identify the actual reality of the modern information systems used in the sports clubs participating in the Premier League by building a new scale according to scientific and methodological foundations. Research in a deliberate way represented in the administrative bodies of the Premier League clubs, which number (20) clubs, and the sample of the research was represented by a percentage (97.7) on which the procedures for building a scale of modern information systems were applied, from which the data that is adopted in diagnosing the actual reality was extracted. reached a set of conclusions, where there was a significant degree and arithmetic mean greater than the hypothetical mean in some of the axes that were included in the scale such as the hardware and software axis, while in other areas such as electronic archiving, communications, networks, information security, procedures and human resources with specialization, the results were insignificant, which This indicates the lack of seriousness of the clubs in applying an information system capable of improving the work of the administrative bodies, which is reflected in the club’s performance. The researchers recommend the relevant authorities search the clubs to develop their information systems and train their employees through specialized courses to keep pace with the rapid development in technology and informatics in the world.